2021
DOI: 10.3390/polym13183101
|View full text |Cite
|
Sign up to set email alerts
|

3D/4D Printing of Polymers: Fused Deposition Modelling (FDM), Selective Laser Sintering (SLS), and Stereolithography (SLA)

Abstract: Additive manufacturing (AM) or 3D printing is a digital manufacturing process and offers virtually limitless opportunities to develop structures/objects by tailoring material composition, processing conditions, and geometry technically at every point in an object. In this review, we present three different early adopted, however, widely used, polymer-based 3D printing processes; fused deposition modelling (FDM), selective laser sintering (SLS), and stereolithography (SLA) to create polymeric parts. The main ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(144 citation statements)
references
References 226 publications
(345 reference statements)
1
101
0
Order By: Relevance
“…Smart or stimulus-responsive material is the other most critical component of 4D printing. The ability of these materials is well-defined by material properties: multifunctional, smart decision making, self-sensing, sensitivity, shape memory, self-adaptability, and self-repair [70][71][72]. A demonstration of a 4DP method is shown in Figure 7 where variations of 4D structures were fabricated to demonstrate the effectiveness of the method.…”
Section: Four-dimensional Printing (4dp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Smart or stimulus-responsive material is the other most critical component of 4D printing. The ability of these materials is well-defined by material properties: multifunctional, smart decision making, self-sensing, sensitivity, shape memory, self-adaptability, and self-repair [70][71][72]. A demonstration of a 4DP method is shown in Figure 7 where variations of 4D structures were fabricated to demonstrate the effectiveness of the method.…”
Section: Four-dimensional Printing (4dp)mentioning
confidence: 99%
“…Stimulus-responsive materials that alter their shape, size or functional properties under certain stimuli such as solvent, pH, temperature, electricity, light, etc. are known as smart materials [70,76,77]. In other words, smart materials are materials that respond to changes in their environment and then undergo a material property change.…”
Section: Smart Materialsmentioning
confidence: 99%
“…Additive manufacturing offers engineers new opportunities to produce components of great complexity that were hitherto impossible to manufacture using conventional techniques. Additive manufacturing offers many other advantages, including reduced lead times, on-demand manufacturing, increased supply chain proficiency, shorter times to market and reduced waste [6][7][8][9][10]. Individual build times for complex components can be relatively long, often being measured in many hours or even days.…”
Section: Introductionmentioning
confidence: 99%
“…A parametric study of the influence of FDM printing parameters revealed a decrease of more than 97% in void density when the layer height decreased from 0.3 to 0.1 mm, proving the paramount importance of this variable [12]. Additionally, FDM has proven to be a fast printing process that allows low part production cost and the use of a reasonable variety of materials, while presenting a poor surface finish and sometimes requiring support structures [14]. Surface roughness is generally reduced with a reduction in layer thickness during printing and/or by applying post-mechanical treatments like polishing/abrasive grinding, as well as by chemical methods such as acetone in vapor and liquid form [13].…”
Section: Introductionmentioning
confidence: 99%